Psychometric adaptation of the questionnaire of attributional styles - Matalinares Calvet, María (2009)
The present study had as objective to analyze the validity and reliability of the Questionnaire of Attributional Styles (QAS) of Alonso and Sanchez (1992). It was worked with 324 subjects from 14 to 16 years, of both sexes, of 4 º and 5 º degree of secondary education. The results demonstrated that scores obtained through the QAS are reliable. Equally, it is possible to conclude that the above mentioned test possesses construct validity, since judges’ criteria and the correlations of each block with the module reach significant values, matrix of correlations reports significant associations between areas and the factorial analysis demonstrates existence of two factors.